Incidência das trajetórias e ciclos de vida na construção do papel e identidade laboral - Carlos Díaz Canepa (Universidade do Porto, 2013)
This article will review some aspects related to the influence of life paths, especially of educational socialization on work role identity configuration. The postulate is that the final educational systems, in which subjects have been socialized, have an impact in the future construction of professional role identity. Data derived from a research on role identity in Metro drivers of Santiago, Chili is studied. Some differences in role identity contents, representations and structures of life path are shown in relation to the final educational system of the drivers.